An experimental method for measuring the spectral absorption coefficient of non-scattering semitransparent media. (March 2019) - Moore, Travis J.
Highlights: Measurement method of spectral absorption coefficient of semitransparent media. Treatment of mathematical model of radiative transfer in semitransparent media. Spectral absorption coefficient of fused silica. Spectral absorption coefficient of aluminum nitride. Abstract: Semitransparent media are those into which electromagnetic waves can penetrate a considerable distance. The spectral absorption coefficient is an important property of non-scattering, semitransparent materials because it describes the degree to which radiative energy is absorbed and emitted by the material. Knowledge of the spectral absorption coefficient is critical for accurate modeling and analysis of applications of semitransparent media. An experimental method for measuring the spectral absorption coefficient of semitransparent media using FTIR spectroscopy is described. Blackbody radiation at different temperatures is transmitted through a semitransparent sample into an FTIR spectrometer. A mathematical model of the radiative heat transfer in the sample is developed to establish a linear spectral instrument response function relating the irradiation on the spectrometer detector to the output signal. The spectral absorption coefficient of a semitransparent material is calculated from the ratio of the slopes of the instrument response functions for two samples of the material with different thicknesses. The estimated spectral absorption coefficient using the proposed method is largely insensitive to the refractive index for media with optically smooth surfaces but, for media with diffuse surfaces, the method is highly dependent on the accuracy with which the refractive index is known. The method is used to calculate the spectral absorption coefficient of both fused silica and aluminum nitride at room temperature in the near to mid-infrared region. There is generally good correlation between the results obtained using the described method and those of other methods.